Dietary approaches to stop hypertension (DASH) diet and blood pressure reduction in adults with and without hypertension: a systematic review and meta-analysis of randomized controlled trials. (25th November 2020) - Filippou, C; Thomopoulos, C; Mihas, C; Dimitriadis, K; Sotiropoulou, L; Siafi, E; Zammanis, I; Dimitriadi, M; Chrysochoou, C; Nihoyannopoulos, P; Tousoulis, D; Tsioufis, C
Abstract: Background: The dietary approaches to stop hypertension (DASH) diet is recognized as an effective dietary intervention to reduce blood pressure (BP). However, among randomized controlled trials (RCTs) investigating the DASH diet mediated BP reduction, there are significant methodological and clinical differences. Purpose: The purpose of this study was to comprehensively assess the effect of the DASH diet on BP levels in adults with and without hypertension, accounting for underlying methodological and clinical confounders. Methods: We systematically searched Medline and the Cochrane Collaboration Library databases and identified 30 RCTs (n=5, 545 participants) that investigated the BP effects of the DASH diet compared to a control diet in hypertensive and non-hypertensive adults. Both random-effects and fixed-effect models were used to calculate the mean attained systolic BP (SBP) and diastolic BP (DBP) differences during follow-up. Subgroup and meta-regression analyses were also conducted. Results: The DASH diet reduced SBP and DBP significantly more compared to the control diet (difference in means: −3.2 mm Hg; 95% CI: −4.2, −2.3; P<0.001, and −2.5 mm Hg; 95% CI: −3.5, −1.5; P<0.001, respectively). Hypertension status did not modify the effect on BP reduction. The DASH diet compared to the control diet reduced SBP levels to a higher extent in trials with sodium intake >2, 400 mg/day compared to trials with sodium intake ≤2, 400 mg/day, while both SBP and DBP were reducedmore in trials with mean age <50 years compared to trials of older participants. The quality of evidence was rated as moderate forboth outcomes according to the Grading of Recommendations, Assessment, Development and Evaluation approach. Conclusion: The adoption of the DASH diet was accompanied by significant BP reduction in adults with and without hypertension, while higher daily sodium intake and younger age enhanced the BP-lowering effect of the intervention. This meta-analysis was registered in the International Prospective Register of Systematic Reviews as CRD42019128120. Funding Acknowledgement: Type of funding source: None